Development of multitasking abilities in middle childhood. (February 2022) - Frick, Andrea; Chavaillaz, Alain; Mäntylä, Timo; Kubik, Veit
Abstract: The development of multitasking abilities was investigated in relation to working memory capacity, sustained attention, inhibition, and task switching. Using a new touch-screen task, 90 children aged 7–10 years were asked to monitor several timers running at different paces, and to press a button whenever a timer had completed its cycle. Results showed that a significant part of the variance in children's multitasking performance was explained by age, and performance increased significantly until about 8–9 years. Multitasking performance was generally affected by the number of tasks, but even more so in younger children. Sustained attention explained a significant part of the variance in triple-, but not dual-task performance; visuospatial working memory capacity explained variance in dual- and triple-task performance, even after controlling for age. In conclusion, multitasking develops considerably in middle childhood and may involve different processes than dualtasking. Highlights: The development of multitasking abilities was investigated in 7- to 10-year-olds. Multitasking performance increased significantly from 7 to about 9 years of age. Multitasking performance was affected by the number of tasks. Younger children showed larger performance costs with more than two tasks. Sustained attention and working memory capacity explained variance in performance.